Tradisi Mappadekko dalam Mempertahankan Solidaritas Para Petani di Desa Kalebarembeng Kabupaten Gowa - Nur Hafsah Nasir; Darman Manda (Rayhan Intermedia, 2023)
The research aims to find out; 1). The Process of the Mappadekko Tradition in Kalebaremeng Village, Gowa Regency. 2). The Function of Tradition in the Daily Life of the Farming Community in Kalebarembeng Village, Gowa Regency. 3). Values ​​contained in the Mappadekko Tradition in Kalebaremeng Village, Gowa Regency. Based on the research results show that; 1). What is the Process of the Mappadekko Tradition in Kalebaremeng Village, Gowa Regency. 2). What is the Function of the Mappadekko Tradition in the Daily Life of the Farming Community in Kalebarembeng Village, Gowa Regency. 3). What values ​​are contained in the Mappadekko Tradition in Kalebaremeng Village, Gowa Regency. The research used is a descriptive type using qualitative data. The validity test was carried out by triangulation technique. Techniques of data analysis and examination of conclusions. The informants of this research are people who are ready to answer the researcher's questions, namely the farming community who still carry out the mappadekko tradition. Primary data was obtained through observation and interviews with informants. While secondary data obtained through literature study in the form of books, journals and so on related to the problem under study. This study uses the theory of community solidarity.